Pengaruh Pemahaman Agama terhadap Kinerja Guru Madrasah Ibtidaiah di Kota Manado - Rivai Bolotio (Institut Agama Islam Negeri (IAIN) Manado, 2017)
ABSTRACT, This study aims to examine the influence of religious understanding on the performance of Madrasah Ibtidaiah teachers in Manado City. The method used in this research is correlational quantitative. This research is conducted in Madrasah Ibtidaiah in Manado City with the sample size of 96, selected from 127 teachers using proportional stratified random sampling. Data collection is done by using test and nontest instruments. The test is used to collect data on religious understanding and the nontest is used to collect the data of practice and performance. The collected data are then analyzed using descriptive analysis and path analysis. The results of this study indicate that religious understanding has a positive direct effect on teacher performance. To improve teachers’ performance, the efforts made, in relation to these variables, include improving teachers’ religious understanding by renewing teachers’ religious knowledge by strengthening faith and devotion to God, and increasing selfawareness that obedience and sincerity in applying it are inevitable.Keywords: Religious understanding, performance, teachersPengaruh Pemahaman Agama terhadap Kinerja Guru Madrasah Ibtidaiah di Kota Manado